K Fertilizers Reduce the Accumulation of Cd in Panax notoginseng (Burk.) F.H. by Improving the Quality of the Microbial Community - Shi, Yue; Qiu, Lisha; Guo, Lanping; Man, Jinhui; Shang, Bingpeng; Pu, Rongfeng; Ou, Xiaohong; Dai, Chunyan; Liu, Pengfei; Yang, Ye; Cui, Xiuming (Frontiers in Plant Science, 2020)
The high background value of cadmium (Cd) in the Panax notoginseng planting soil is the main reason for the Cd content in P. notoginseng exceeding the limit standards. The main goal of this study was to reveal the mechanism by which potassium (K) reduces Cd accumulation in P. notoginseng from the perspective of the influences of soil microbial communities on soil pH, total organic matter (TOM) and cation exchange capacity (CEC). Pot experiments were conducted to study the effects of different types and amounts of applied K on the Cd content in P. notoginseng, and on the soil pH, TOM, CEC and bioavailable Cd (bio-Cd) content in soil. Field experiments were conducted to study the effects of K2SO4 fertilizer on the microbial community, and its correlations with the soil pH, TOM and CEC were analyzed. A moderate application of K2SO4 (0.6 g·kg-1) was found to be the most optimal treatment for he reduction of Cd in the pot experiments. The field experiments proved that K fertilizer (K2SO4) alleviated the decreases in pH, TOM and CEC, and reduced the content of bio-Cd in the soil. The application of K fertilizer inhibited the growth of Acidobacteria, but the abundances of Mortierellomycota, Proteobacteria and Bacteroidetes were promoted. The relative abundances of Acidobacteria and Proteobacteria in the soil bacteria exhibited significant negative and positive correlations with pH and CEC, respectively. In contrast, the relative abundance of Mortierellomycota was found to be positively correlated with the pH, TOM and CEC. The bio-Cd content was also found to be positively correlated with the relative abundance of Acidobacteriia but negatively correlated with the relative abundances of Proteobacteria and Mortierellomycota. The application of K fertilizer inhibited the abundance of Acidobacteria, which alleviated the acidification of the soil pH and CEC, and promoted increase in the abundances of Mortierellomycota, Proteobacteria and Bacteroidetes, which ultimately increased the soil TOM and CEC. Soil microorganisms were found to mitigated decreases in the soil pH, TOM and CEC and reduced the bio-Cd content in the soil, which significantly reduced the accumulation of Cd in P. notoginseng.